Innovations Creation Process: CEO and Board of Directors Roles - Mariia Evdokimova (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2021)
There are innovation creation process, innovations’ classifications, and measures considered in the paper. Recently focus on the literature moving from innovations relationship with financials to the role of people. This review considers board of directors group characteristics and CEO individual characteristics (the part of which impacts only firms from innovative industries) significant for innovation creation. The paper predicts investment in innovation, innovation outcome, and optimal for shareholders’ wealth board of directors’ type in dependence on CEO individual characteristics.